Mathematical model attitude estimation using Kalman filter technique for low earth orbit satellite - Nor Hazadura, Hamzah; Sazali, Yaacob, Prof. Dr.; Teoh, Vil Cherd; Siti Maryam, Harun; Hariharan, Muthusamy; Mohamad Nazri, Dol Bahar; Norhizam, Hamzah (Universiti Malaysia Perlis (UniMAP), 2012)
International Conference on Man Machine Systems (ICoMMS 2012) organized by School of Mechatronic Engineering, co-organized by The Institute of Engineer, Malaysia (IEM) and Society of Engineering Education Malaysia, 27th - 28th February 2012 at Bayview Beach Resort, Penang, Malaysia.